2016
DOI: 10.1097/mao.0000000000001236
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Telemedicine in Auditory Rehabilitation

Abstract: Objective The purpose of this study was to assess the feasibility and effectiveness of live telemedicine applications in hearing amplification and cochlear implantation. Data Sources and Study Selection A systematic search was performed in PubMed, MEDLINE, PsychINFO, CINALH, and Web of Science to identify peer-reviewed research. Inclusion criteria were titles containing words from the search terms (1) audiology, otolaryngology, and hearing impairment, (2) rehabilitative methods, and (3) telemedicine. Exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 40 publications
(44 reference statements)
2
38
1
8
Order By: Relevance
“…Three previous systematic reviews of the literature on tele-audiology have been published and examined the following: (i) the use of telehealth in audiology (Swanepoel & Hall 2010), (ii) telehealth studies in hearing sciences and speech-language (Molini-Avejonas, Rondon-Melo, Amato & Samelli, 2015), and (iii) the feasibility and effectiveness of synchronous telehealth in hearing rehabilitative services (Bush, Thompson, Irungu, & Ayugi, 2016). These reviews concluded that (a) there is a lack of protocols and models of service delivery for specific populations, (b) there are resource constraints e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Three previous systematic reviews of the literature on tele-audiology have been published and examined the following: (i) the use of telehealth in audiology (Swanepoel & Hall 2010), (ii) telehealth studies in hearing sciences and speech-language (Molini-Avejonas, Rondon-Melo, Amato & Samelli, 2015), and (iii) the feasibility and effectiveness of synchronous telehealth in hearing rehabilitative services (Bush, Thompson, Irungu, & Ayugi, 2016). These reviews concluded that (a) there is a lack of protocols and models of service delivery for specific populations, (b) there are resource constraints e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Para Correia et al (2014) a telessaúde na região norte/nordeste apresenta um grande desafio quanto à qualidade da conectividade, desafio também apontado pelo estudo de revisão sistemática de Molina-Alvejonas, et al (2015) e outros autores. (RAVI et al, 2018;BUSH et al, 2016).…”
Section: Discussionunclassified
“…A utilização dos recursos de telessaúde para os serviços de reabilitação em Audiologia tem demonstrado grandes avanços. Algumas das questões importantes a serem solucionadas para capitalizar ainda mais o potencial destas ferramentas são as limitações da internet de banda larga nas regiões remotas e o custo-efetividade dos serviços oferecidos (BUSH et al, 2016).…”
Section: Introductionunclassified
“…Klinische Untersuchungen könnten auch bei der Nachsorge, wie bereits im Kapitel Screening beschrieben, über sog. Otoskopie-Apps abgebildet werden [90]. Die wahrscheinlich interessantesten Möglichkeiten bei Betrachtung der Digitalisierung ergeben sich für die audiologische Nachsorge, die regelhaft bei Auffälligkeiten in der technischen Nachsorge stattfindet.…”
Section: Lösungsansätze In Der Ci-nachsorgeunclassified